Solubilized delivery of paliperidone palmitate by d- alpha-tocopheryl polyethylene glycol 1000 succinate micelles for improved short-term psychotic management - Muthu M.S.; Sahu A.K.; Sonali; Abdulla A.; Kaklotar D.; Rajesh C.V.; Singh S.; Pandey B.L. (My University, 2025)
The objective of this work was to formulate paliperidone palmitate-loaded d-alpha-tocopheryl polyethylene glycol 1000 succinate (Vitamin E TPGS or TPGS) micelles for improved antipsychotic effect during short-term management of psychotic disorders. Vitamin E TPGS micelles containing paliperidone palmitate were prepared by the solvent casting method and control paliperidone palmitate formulations were prepared by simple sonication method. The prepared micelles and control paliperidone palmitate formulations were evaluated for different parameters. Particle sizes of prepared micelles, control paliperidone palmitate formulations were determined at 25 °C by dynamic light scattering technique and external surface morphology was determined by transmission electron microscopy analysis. The encapsulation efficiency was determined by spectrophotometery. In-vitro release studies of micelles and control formulations were carried out by dialysis bag diffusion method. The particle sizes of the paliperidone palmitate-loaded TPGS micelles were 26.5 nm. About 92% of drug encapsulation efficiency was achieved with micelles. The drug release from paliperidone palmitate-loaded TPGS micelles was sustained for more than 24 h with 40% of drug release. The TPGS product, i.e. paliperidone palmitate-loaded micelles, resulted in nano-sized delivery, solubility enhancement and permeability of the micelles which provided an improved and prolonged anti-psychotic effect in comparison to control paliperidone palmitate formulation. © 2014 Informa Healthcare USA, Inc.